1973
DOI: 10.1111/j.1432-1033.1973.tb02972.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rat‐Liver Mitochondrial Ribosomes Highly Active in Poly(U)‐Directed Polyphenylalanine Synthesis

Abstract: The procedure used to obtain mitochondrial ribosomes from rat liver highly active in catalyzing a poly(U)-dependent polyphenylalanine synthesis is described.Two kinds of particles with sedimentation coefficients of 80-S and 55-5, present in the mitochondrial lysate, are able to catalyze protein synthesis in vitro.Sensitivity to specific inhibitors of protein synthesis demonstrates that the activity of 55-5 particles is only of niitochondrial origin whereas that of 80-5 particles is partly due to mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
1

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
1
6
1
Order By: Relevance
“…The findings of other research groups who achieved activity in vitro with 55-S ribosomes and supernatant fraction from E. coli [15,16] are in apparent contradiction to our results. However, no evidence was presented in these investigations that the mitochondrial ribosomes treated with only 100 mM KCI were really free of endogenous elongation factors.…”
contrasting
confidence: 57%
“…The findings of other research groups who achieved activity in vitro with 55-S ribosomes and supernatant fraction from E. coli [15,16] are in apparent contradiction to our results. However, no evidence was presented in these investigations that the mitochondrial ribosomes treated with only 100 mM KCI were really free of endogenous elongation factors.…”
contrasting
confidence: 57%
“…55-S mitochondrial ribosomes were isolated as described elsewhere [5], the rRNAs were extracted from the ribosomes with a SDS/phenol procedure. Poly(A)-containing mtRNA was obtained by oligo(dT) cellulose chromatography, as presented in detail recently [6].…”
Section: Preparation Of Mitochondrial Rna From Rat Livermentioning
confidence: 99%
“…The exact molecular mechanism of this resistance is not known but it has been suggested that either some aspect of the secondary structure of the messenger (poly(U)) or the hydrophobicity or aromaticity of the amino acid (phenylalanine) allows this aminoacyl-tRNA to compete successfully with chloramphenicol for occupation of the A site on the ribosome (Pestka, 1977). Nonetheless, Ibrahim et al (1974) and Greco et al (1973) both reported that chloramphenicol inhibited poly(U)-directed polypeptide synthesis by mitochondrial ribosomes vitro. Avadhani and Rutman (1974) reported that in an S-25 prepared from Ehrlich acites cell mito chondria, synthesis of polyphenylalanine was inhibited by chloramphenicol.…”
Section: Ribosomes Active In Polypeptide Synthesismentioning
confidence: 99%
“…The preparations were free of cytoplasmic and bacterial contamination but were not active in in vitro polypeptide synthesis. In 1973, Ibrahim et al, using a modification of the procedure of O'Brien and Kalf (1967), and Greco et al (1973), were able to isolate rat liver mitochondrial ribosomes which were active in poly(U)-directed polyphenylalanine synthesis and which were more active than the preparation of O'Brien and Kalf in tiie peptidyl transferase assay. Both systems used ^ coli supernatant factors and were inhibited by low levels of chloramphenicol.…”
mentioning
confidence: 99%
See 1 more Smart Citation